Evaluation of sea surface temperature from ocean reanalysis products over the North Indian Ocean - Rahman, Raheema; Rahaman, Hasibur (Frontiers in Marine Science, 2024)
Ocean and sea-ice reanalyses (ORAs, or ocean syntheses) are reconstructions of the ocean and seaice states using an ocean model integration constrained by atmospheric surface forcing and ocean observations via a data assimilation method. Ocean reanalyses are a valuable tool for monitoring and understanding long-term ocean variability at depth, mainly because this part of the ocean is still largely unobserved. Sea Surface Temperature (SST) is the key variable that drives the air-sea interaction process on different time scales. Despite improvements in model and reanalysis schemes, ocean reanalyses show errors when evaluated with independent observations. The independent evaluation studies of sea surface temperature (SST) from ocean reanalysis over the Indian Ocean are limited. In this study, we evaluated the SST from 10 reanalysis products (ECCO, BRAN, SODA, NCEP-GODAS, GODAS-MOM4p1, ORAS5, CGLORS, GLORYS2V4, GLOSEA and GREP) and five synthetic observation products (COBE, ERSST, OISST, OSTIA, HadISST) and pure observation based product AMSR2 for 2012-2017 with twelve (12) in-situ buoy observations (OMNI) over the Arabian Sea and Bay of Bengal. Even though the reanalysis and observational products perform very well in the open ocean, the performance is poorer near the coast and islands. The reanalysis products perform comparatively better than most of the observational products. The COBE and OISST performed better among the observational products in the northern Indian Ocean. GODAS-MOM4p1 performed best among the reanalysis products, often surpassing the observational products. ECCO shows poorer performance and higher bias in the Bay of Bengal. Comparing the BRAN daily and monthly SST, the monthly SST performance of reanalysis is better than the daily time scale.